INTEGRATING GREEN EDUCATION INTO SCIENCE LEARNING TO FOSTER ENVIRONMENTAL AWARENESS IN ELEMENTARY SCHOOLS - Devi Anggi Friani; Marheni Rayung Puspaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to describe the integration of green education into science learning as an effort to foster environmental awareness among elementary school students. The research employed a descriptive qualitative approach involving a science teacher and fourth-grade students at Elementary School in Magetan District. Data were collected through observation, in-depth interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that science learning integrated with green education is characterized by contextual, experiential, and environmentally oriented learning activities. The learning process includes planning environment-based project modules, implementing active learning strategies, and conducting authentic assessments covering cognitive, affective, and psychomotor domains. The integration of green education has been shown to increase students’ environmental awareness and behaviors, such as properly disposing of waste, conserving water and energy, and participating in school greening programs. Therefore, integrating green education into science learning is an effective strategy to cultivate ecological character and support sustainable education at the elementary school level.